Secondary trauma and posttraumatic growth among mental health clinicians involved in disaster relief activities following the 2011 Tohoku earthquake and tsunami in Japan. Issue 4 (1st October 2020) - Tominaga, Yoshiki; Goto, Toyomi; Shelby, Janine; Oshio, Atsushi; Nishi, Daisuke; Takahashi, Satoshi
ABSTRACT: Following the Tohoku earthquake and tsunami disaster, 230 mental health clinicians participated in a disaster relief mission and then responded to an online survey assessing their posttraumatic growth (PTG), as well as other variables and outcomes related to their work. Findings revealed that post-mission intrusion severity significantly predicted total PTG at 2 months following the relief activities. Previous knowledge/skill was also an important variable, positively predicting CS and negatively predicting burnout. One-fifth of clinicians reported clinically significant trauma symptoms immediately following their work but few respondents reported clinically significant symptoms two months following their relief work. However, severe intrusion and avoidance symptomatology immediately following of the relief mission was associated with greater levels of compassion fatigue. The implications of this study are that adequate preparation of clinicians and social/professional support play important roles in promoting satisfaction with disaster-relief work, and training/knowledge reducing burnout reactions and promoting satisfaction with disaster-relief work. In addition, disaster-related intrusion symptoms may be part of a normative, adaptive process after disaster relief activities and can co-exist with or promote PTG.